A Concept Analysis of Moral Injury in Ukrainian National Guard Service Members’ Narratives: A Clinical Case Study - Zasiekina, Larysa; Kokun, Oleg; Kozihora, Mariia; Fedotova, Tetiana; Zhuravlova, Olena; Bojko, Martha (Lesya Ukrainka Eastern European National University, 2022)
Moral injury is a relatively new construct which is strongly associated with PTSD but which also has distinctive features that may not overlap with PTSD. There is a growing body of literature that recognises moral injury as emotional distress and sufferings arising from a transgression of one’s core moral principles or ethical beliefs and aligned with feelings of shame and guilt. A great number of moral injury research is represented by theoretical and qualitative studies vs biopsychosocial approach towards conceptualizing PTSD. However, a systematic understanding of how potentially moral injurious events contribute to moral injury symptoms is still lacking. Of particular concern is moral injury of military personnel exhibiting PTSD symptoms during and after wartime. This study utilizes the concept analysis model (Walker & Avant, 2011) to explore and assess the attributes, antecedents, consequences and empirical referents of moral injury in Ukrainian National Guard service members, who are protecting the northern Ukrainian border with Belarus and defending military objects during the 2022 full-scale invasion of Ukraine by Russian troops. The research uses narrative case studies collected from National Guard soldiers in Ukraine as part of our combatants' moral injury broader project. Initial results of this study indicate mechanisms of developing moral injury symptoms with comorbidity of depression, generalized anxiety, and PTSD in National Guard service members during wartime. The findings of the current study have important theoretical and practical implications in terms of better understanding the causal relations of moral injury and enhancing clinical practice and holistic treatment approach for National Guard soldiers. Acknowledgements This research was financially supported by the Ministry of Education and Science of Ukraine within the project “Moral Injury and Healing of Combatants: Neuropsychological Correlates and Psychological Interventions” (2022-2023), 0122U000945. We would also like to acknowledge and thank the Ukrainian National Guard participants for their time and willingness to share their experiences with the research team.
Keywords: National Guard service members; moral injury; concept analysis; narratives